2018
DOI: 10.1210/er.2018-00049
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the Circadian Clock to Homeostasis: The Role of Period in Timing Physiology

Abstract: A plethora of physiological processes show stable and synchronized daily oscillations that are either driven or modulated by biological clocks. A circadian pacemaker located in the suprachiasmatic nucleus (SCN) of the ventral hypothalamus coordinates 24-hour oscillations of central and peripheral physiology with the environment. The circadian clockwork involved in driving rhythmic physiology is composed of various clock genes that are interlocked via a complex feedback loop to generate precise yet plastic osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 325 publications
0
34
0
Order By: Relevance
“…Melatonin is strongly regulated by light/dark cycle with high levels during the night in all vertebrates. This fundamental rhythmic endocrine signal for darkness in the body is controlled by the master clock in the SCN and mainly by the Period gene (Per1) that has been shown to cycle rhythmically in the pineal gland [74]. For instance, McHill et al [75] found that, on average, obese individuals consumed most of their calories an hour closer to melatonin onset (biological marker of impending sleep onset) compared to lean individuals.…”
Section: Meal Timingmentioning
confidence: 99%
“…Melatonin is strongly regulated by light/dark cycle with high levels during the night in all vertebrates. This fundamental rhythmic endocrine signal for darkness in the body is controlled by the master clock in the SCN and mainly by the Period gene (Per1) that has been shown to cycle rhythmically in the pineal gland [74]. For instance, McHill et al [75] found that, on average, obese individuals consumed most of their calories an hour closer to melatonin onset (biological marker of impending sleep onset) compared to lean individuals.…”
Section: Meal Timingmentioning
confidence: 99%
“…In a DST shift effect analysis, one should keep in mind that there are two distinct phenomena in play: (1) the natural variation of day length, the amount of light over the year, and the daily sunlight intensity cycle affects the human circadian clock, behavior, and numerous diseases [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and; (2) the disruption of individuals' daily schedule due to the DST shift. Our analyses were designed to target the effects associated with the latter, adjusting for the former with negative controls.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Currently, several core circadian genes, also known as circadian clock genes, have been identified in humans (13): ARNTL (aryl hydrocarbon receptor nuclear translocator like, also identify in brain and muscle as Arnt-like protein-1, BMAL1) (14, 15), CLOCK (clock circadian regulator) (16), CRY1 (cryptochrome circadian clock 1), CRY2 (cryptochrome circadian clock 2) (17), PER1 (period circadian clock 1), PER2 (period circadian clock 2), PER3 (period circadian clock 3) (1820), CSNK1E (casein kinase I epsilon) (6, 21), NPAS2 (neuronal PAS domain protein 2) (22, 23), NR1D1 (nuclear receptor subfamily 1 group D member 1 also called Rev-Erb alpha) (24, 25), NR1D2 (nuclear receptor subfamily 1 group D member 2 also referred to Rev-Erb beta) (26), RORA (RAR related orphan receptor A) (27) and TIMELESS (timeless circadian clock) (28, 29).…”
Section: Circadian Clock Mechanism Clock Genes and Cancermentioning
confidence: 99%